2019
DOI: 10.3390/pharmaceutics11110561
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of UDCA-Containing Oral Formulation in Mice for the Treatment of Wet Age-Related Macular Degeneration

Abstract: As a posterior ocular disease, wet age-related macular degeneration (WAMD) has been known to be related to vision loss, accompanying ocular complications. The intravitreous injection of VEGF antibodies has been reported to be an effective treatment to relieve symptoms of WAMD. However, the limitations of this treatment are high costs and invasiveness. For this reason, oral delivery route can be considered as a cost-effective way and the safest method to deliver drug molecules to the eyes. Accordingly, ursodeox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Due to the key role of VEGF in promoting RNV in the ischemic retina [45], UDCA's anti-angiogenic effects in OIR mice could be attributable, at least in part, to its effects in halting the VEGF-STAT3 axis by attenuating oxidative/nitrative stress signals in the ischemic retina. Similarly, UDCA has been shown to improve other ocular pathologies that involve excessive VEGF action (or oxidative stress) such as wet age-related macular degeneration [46] and diabetic retinopathy [40], thus, further highlighting the significant impact of UDCA on VEGF signaling.…”
Section: Discussionmentioning
confidence: 95%
“…Due to the key role of VEGF in promoting RNV in the ischemic retina [45], UDCA's anti-angiogenic effects in OIR mice could be attributable, at least in part, to its effects in halting the VEGF-STAT3 axis by attenuating oxidative/nitrative stress signals in the ischemic retina. Similarly, UDCA has been shown to improve other ocular pathologies that involve excessive VEGF action (or oxidative stress) such as wet age-related macular degeneration [46] and diabetic retinopathy [40], thus, further highlighting the significant impact of UDCA on VEGF signaling.…”
Section: Discussionmentioning
confidence: 95%
“…This study showed that UDCA formulation not only down-regulated VEGF expression and reduced CNV vascularity and size, but also promoted the functional recovery of the mice retinas according to electroretinography evaluation. Therefore, the authors suggest that UDCA oral formulation could be used as a supplement in cases of exudative AMD thanks to it being a safe and cost-effective way to deliver drug molecules to the eyes [ 132 ].…”
Section: New Therapeutics For Amdmentioning
confidence: 99%
“…Woo, et al demonstrated that UDCA and its derivative, TUDCA, when intraperitoneally injected to the laser-treated rat model, could effectively suppress early VEGF elevation in the retina which inhibits the upregulation of VEGF and eventually results in the reduction in CNV size and vascularity, suggesting the possibility of treating CNV [ 101 ]. In a recent study, a mouse model of laser-induced CNV was used to test the efficacy of YSB201 (an aqueous solution of UDCA) in the treatment of AMD [ 102 ]. Results indicated that the YSB201 treatment inhibited the return of angiogenesis to the normal choroidal tissue condition.…”
Section: Pharmacological Effects Of Bile Acids In Ocular Diseasementioning
confidence: 99%
“…Additionally, while YSB201 treatment at 125 mg/kg/day led to the recovery of retinal function post-injury, the higher dose of YSB201 treatment at 250 mg/kg/day did not yield significantly higher recovery effects. The results of the study specifically describe the inhibitory effects of UDCA formulation on CNV with functional recovery in mice retinas [ 102 ]. Taken together, these results suggest that UDCA could be used as a potent supplement for the cure of AMD and related retinal complications.…”
Section: Pharmacological Effects Of Bile Acids In Ocular Diseasementioning
confidence: 99%